Teaching the Proper Push-up Position: Editor: Ferman Konukman. Issue 7 (2nd September 2018) - Hewit, Jennifer; Jaffe, Daniel; Bedard, Alexander
Abstract : The ability to maintain proper body positioning throughout the performance of a push-up is important in order to build strength and to limit the potential for injury. This article describes what to look for when observing students' push-up technique.